Characterizing the local vectorial electric field near an atom chip using Rydberg-state spectroscopy - Cisternas San Martin, Nataly; Lochead, Graham (Physical review, 2017)
We use the sensitive response to electric fields of Rydberg atoms to characterize all three vector components of the local electric field close to an atom-chip surface. We measured Stark-Zeeman maps of S and D Rydberg states using an elongated cloud of ultracold rubidium atoms (temperature T∼2.5μK) trapped magnetically 100μm from the chip surface. The spectroscopy of S states yields a calibration for the generated local electric field at the position of the atoms. The values for different components of the field are extracted from the more complex response of D states to the combined electric and magnetic fields. From the analysis we find residual fields in the two uncompensated directions of 0.0±0.2 and 1.98±0.09 V/cm. This method also allows us to extract a value for the relevant field gradient along the long axis of the cloud. The manipulation of electric fields and the magnetic trapping are both done using on-chip wires, making this setup a promising candidate to observe Rydberg-mediated interactions on a chip.